(untitled) (Canadian Medical Education Journal, 2024)
Implication Statement ACCESS, a student-led mentorship program affiliated with Schulich School of Medicine & Dentistry, demonstrates a practical, effective approach to addressing inequity in medical education. ACCESS provides personalized, zero-cost mentorship to equity-deserving applicants who face social, financial, and medical barriers that result in underrepresentation in medical school. Our mentorship model showcases significant success in application and interview outcomes, as well as positive feedback from participants. Here, we offer a replicable blueprint for medical schools across Canada. This paper highlights the effectiveness of student-led initiatives in promoting diversity and inclusion in healthcare education and aims to inspire similar programs, fostering a more diverse and inclusive future healthcare workforce.